Accounting Record Training for MSMEs in Batu Merah Village - Risakotta, Kathleen Asyera; Sapulette, Shella Gilby (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This community service aims to enhance MSMEs' financial management skills in Batu Merah Village, Ambon, by providing simple accounting training. It seeks to improve their ability to maintain accurate records and prepare financial reports, addressing business management challenges effectively. Method: Training sessions on basic accounting principles will be conducted, tailored to MSMEs' needs. Socialization sessions will reinforce understanding. Data collection involves qualitative feedback on training effectiveness and perceived skill improvements. Practical Applications: Improved financial management enables informed decision-making, resource optimization, and easier access to financial services for MSMEs. This fosters their growth and sustainability.Conclusion: By addressing the need for enhanced financial literacy, this research equips MSMEs in Batu Merah Village to navigate financial challenges effectively, contributing to their long-term success and resilience in rural communities.